Home blood pressure monitor use in patients with chronic kidney disease. (2nd September 2016) - Ye, Xiaojing; Shafi, Salman; Negrete, Andrea; Davis, William N.; Sarac, Erdal; Negrete, Alejandro M.; Negrete, Hilmer
Abstract: Home blood pressure monitoring (HBPM) is recommended in patients with chronic kidney disease (CKD) and hypertension (HTN). However, little is known about the use and pattern of HBPM in CKD patients. A cross-sectional study was conducted in an out-patient nephrology clinic. A total of 285 patients participated in the study. Of all patients, 66% reported using HBPM. Self-reported compliance with BP medications (93.9% vs. 85.1%, p 0.03), exercise >3 days/week (45.9 vs. 26.3%, p <0.001) and dietary sodium restriction (85.6% vs. 71.6%, p < 0.001) were more common in HBPM users vs. non-HBPM users. Most patients with HBPM used upper arm cuff (82.3%), reported receiving education on correct use of HBPM (82.5%), had perception that home BP was controlled (75.4%) and believed that HBPM is helpful in managing hypertension (85.4%). Most common reason for not using HBPM was lack of advice by a physician (43.4%). HBPM use is common in patients with CKD and HTN. HBPM users are more likely to follow life-style and dietary modifications for blood pressure control.